ANALISIS PENERAPAN PEMBELAJARAN DIFERENSIASI PROSES MELALUI GAYA BELAJAR SISWA PADA MATERI MENULIS LAPORAN HASIL OBSERVASI - Annisa Aprilia Fitri; Nani Solihati (STKIP Siliwangi, 2023)
This research was conducted to investigate how the application of differentiated process learning through students learning styles is implemented in the material of writing observation report texts. In order to determine this, the research was carried out using a descriptive qualitative method and a literature review analysis so that this study is able to holistically describe various perspectives. The researcher collected data by analyzing diagnostic test results, observations, interviews, and learning product analysis. Based on the diagnostic test analysis, there were three student learning style preferences, namely (1) visual, (2) auditory, and (3) kinesthetic. In the implementation of differentiated process learning, teachers provide different learning stimuli according to the students need. Students with visual learning styles are given stimuli through posters and power point slide shows, auditory learners are given stimuli by listening to the material provided by the teacher as well as students taking turns as speakers (peer tutors and discussions), and kinesthetic learners are given stimuli by arranging puzzles and creating mind maps. The teacher's stimuli based on students learning styles make learning more enjoyable, encourage active student involvement, and foster creativity in students, allowing them to absorb knowledge information to the fullest and develop their innate potential.